2020
DOI: 10.1002/aic.16649
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of polarity on the behavior of mixtures of n‐alkanes with dipolar solvents using polar soft‐statistical associating fluid theory (Polar soft‐SAFT)

Abstract: We present results concerning the phase equilibria and excess properties of binary mixtures of n-alkanes with a range of fluids from low to high dipolar strength, namely 1-hexene, chloroform, dichloromethane, tetrahydrofuran, acetone, dimethylformamide, and N-methyl pyrrolidone modeled by polar soft-statistical associating fluid theory. Polar interactions are considered through the theory of Gubbins and Twu, extended to chainlike fluids by Jog and Chapman, and a priori fixing the polar parameters of the pure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…sPC-SAFT predictions for mixtures containing strong polar compounds require large binary interaction parameters (BIPs) to accurately represent the data. Therefore, several researchers have published work on accounting for these significant dipolar interactions explicitly. ,, It follows that polar effects in the sPC-SAFT EoS can be described by adding a dipolar term in Helmholtz energy as follows …”
Section: Methodsmentioning
confidence: 99%
“…sPC-SAFT predictions for mixtures containing strong polar compounds require large binary interaction parameters (BIPs) to accurately represent the data. Therefore, several researchers have published work on accounting for these significant dipolar interactions explicitly. ,, It follows that polar effects in the sPC-SAFT EoS can be described by adding a dipolar term in Helmholtz energy as follows …”
Section: Methodsmentioning
confidence: 99%
“…It was found that accurate correlation of data can be achieved by these models using a couple of temperaturedependent and system-specific binary adjustable parameters. More recently, Alkhatib et al 30 applied the polar soft-SAFT 31 EoS for modeling phase equilibria in binary systems of nalkanes and several dipolar compounds, including NMP. For the systems n-hexane−, n-heptane−, and n-octane−NMP, the same temperature-independent value of the binary adjustable parameter was used.…”
Section: ■ Introductionmentioning
confidence: 99%